2022
DOI: 10.1002/iid3.634
|View full text |Cite
|
Sign up to set email alerts
|

Precision health diagnostic and surveillance network uses S gene target failure (SGTF) combined with sequencing technologies to track emerging SARS‐CoV‐2 variants

Abstract: Introduction The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic revealed a worldwide lack of effective molecular surveillance networks at local, state, and national levels, which are essential to identify, monitor, and limit viral community spread. SARS‐CoV‐2 variants of concern (VOCs) such as Alpha and Omicron, which show increased transmissibility and immune evasion, rapidly became dominant VOCs worldwide. Our objective was to develop an evidenced‐based genomic surveillanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The O-BA.2 lineage does not have the 69-70 deletion [ 32 ], which correlates with the S protein being recognized by PCR tests as was the case with the Delta variant. In previous studies, samples identified as Omicron (with the exception of the BA.2 lineage and sublineages) were associated with S-gene dropout, similar to what was observed with those samples identified to be Alpha (B.1.1.7 VOC 202012/01) [ 18 , 31 ]. Samples collected and sequenced in this study were associated with the S-gene dropout mirroring the progression of Omicron detection within the population ( Figure 1 and Figure 3 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The O-BA.2 lineage does not have the 69-70 deletion [ 32 ], which correlates with the S protein being recognized by PCR tests as was the case with the Delta variant. In previous studies, samples identified as Omicron (with the exception of the BA.2 lineage and sublineages) were associated with S-gene dropout, similar to what was observed with those samples identified to be Alpha (B.1.1.7 VOC 202012/01) [ 18 , 31 ]. Samples collected and sequenced in this study were associated with the S-gene dropout mirroring the progression of Omicron detection within the population ( Figure 1 and Figure 3 ).…”
Section: Discussionsupporting
confidence: 76%
“…The failure to detect SARS-CoV-2 S-gene in COVID-19 molecular tests is referred to as S-gene dropout or drop-off [ 18 ]. The S-gene was detected in a vast number of samples during wk 36-2021 to wk 49-2021 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many publications have evaluated different approaches to determining the accuracy and applicability of the SGTF in variant detection [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In our study, the sensitivity and specificity values based on WGS VOC determination were in line with previously reported values [ 34 ]; our calculations based on variant-specific PCR, however, were consistently lower than for WGS, indicating a reduced accuracy in lineage classification.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the reason may be, this pandemic has made known that due to deficient molecular surveillance, we were unable to identify and monitor the viral pathogen spread among the community [3].…”
Section: Introductionmentioning
confidence: 99%